Marriage and Religion: Dynamics of Religious Conversion in Marriage and The Advancement of Community Religious Life Perspective of Religious Psychology and Sociology (Study in Lumajang Regency) - Muhammad Aminuddin Shofi (Jurnal Dialog, 2021)
This study analyzes how and why interfaith couples tend to return to their religions after marriage. The results showed that the choice of interfaith couples to embrace their partner’s religion at the time of marriage is necessary, because they saw that their new religion provides attractive rewards (marriage). The discovery of the converters who later reverted to their original religion indicated that the religious conversion was carried out for the purpose of marrying their partners only. There were three reasons for the conversion: a) A strong belief in the original religion so that it is difficult to completely convert to a new religion when getting married. b) Freedom of religious observance given by the spouses and the families becomes social support which makes the converters remain calm and confident about their actions. c) The surrounding environment is also the reason as to why conversion occurs; the religion of the majority of the surrounding community can also influence conversion to the original religion. Penelitian ini akan menganalisis bagaimana dan apa alasan pasangan beda agama melakukan konversi agama kembali pasca perkawinan. Hasil penelitian menunjukkan pilihan pasangan beda agama untuk memeluk agama pasangannya ketika menikah adalah sebuah keniscayaan, sebab mereka melihat agama baru yang dianut memberikan reward yang menarik (menikah). Ditemukannya pelaku konversi yang kemudian kembali menganut agama asal menandakan konversi agama yang dilakukan tidak sungguhan, hanya sebatas untuk dapat mengawini pasangannya. Ada tiga alasan tindakan konversi yang dilakukan informan penelitian: a) Kuatnya keimanan pada agama asal sehingga sulit untuk harus secara total melakukan konversi agama ketika melangsungkan perkawinan. b) Kebebasan dalam menganut agama yang diberikan oleh pasangan dan keluarga menjadi dukungan sosial yang menjadikan pelaku konversi tetap tenang dan percaya diri atas tindakannya. c) Lingkungan sekitar juga menjadi alasan pelaku konversi, agama mayoritas masyarakat sekitar juga dapat mempengaruhi tindakan konversi pada agama semula.